Water symbolism in the work Pleamar de vejez by costarican writer Jorge Marín - Barboza Ramírez, María Isabel (2019)
The following study makes an analysis through the different historical representations and manifestations of water and its importance to mankind. Notably, in the poems written by Jorge Marín, the symbolic representation of this element is analyzed trough his work. The main theme of the poem collection is based in two recurrent topics in literature: life and death and the association with the water element that the lyrical subject establishes regarding this isotopy.